Flow structures and hydrodynamics of unsteady cavitating flows around hydrofoil at various angles of attack - Ju, Dong-mei; Xiang, Chang-le; Wang, Zhi-ying; Li, Jun; Xiao, Nan-xi (Journal of hydrodynamics. Series B, 2018)
This paper investigates the unsteady structures and the hydrodynamics of cavitating flows. Experimental results are presented for a Clark-Y hydrofoil fixed at α = 0°, 5° and 8°, for various cavitation numbers, from subcavitating flow to supercavitation. The high-speed video camera and the particle image velocimetry (PIV) are applied to observe the transient flow structures. Statistics of the cavity lengths, the velocity and vorticity distributions, as well as the turbulent intensities are presented to quantify the unsteady process. Meanwhile, the dynamic measurement system is used to record the dynamic characteristics. The experimental results show that the flow structures and the hydrodynamics of the cavitation vary considerably with various combinations of angles of attack and cavitation numbers. Under various conditions, the cavitation can be generally grouped as the inception cavitation, the sheet cavitation, the cloud cavitation and the supercavitation. The cloud cavitation exhibits noticeable unsteady characteristics. Experimental evidence indicates that the hydrodynamics are clearly affected by the cavitating flow structures, the amplitude of the load fluctuation is much higher in the cloud cavitating cases.